The Scorch trials / 2. - Dashner, James, 1972- (Dashner, James, 1972- Maze runner series., 2015)
Thomas and the Gladers, having solved the Maze, plan on returning to their lives, but instead find the earth a wasteland with Cranks roaming the desert in search of their next meal and they are faced with the challenge of crossing the Scorch in two weeks in order to arrive at a safe haven.